Role of urinary tract infection in development of neonatal pathological unconjugated hyperbilirubinemia - Kumar, Ajay; Batcha, Mohammed Uvaise (Indian Journal of Child Health, 2018)
Introduction: American Academy of Pediatrics recommends investigating for urinary tract infection (UTI) in neonates with conjugated hyperbilirubinemia, but UTI may be associated with unconjugated hyperbilirubinemia also. Objective: The objective of this study was to evaluate the frequency of UTI in initial 4 weeks of life in pathological unconjugated hyperbilirubinemia and to study the effect of treatment of UTI on the course of hyperbilirubinemia in these neonates. Methods: This hospital-based prospective cohort study included 100 consecutive neonates with a gestational age more than or equal to 35 weeks and